Product relatedness and firm exports in China - Sandra Poncet; Felipe Starosta de Waldemar (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
We propose the first evaluation using micro-level data of the expected growth gains from the consistency of activities with local comparative advantage. Using firm level data from Chinese customs over 2000-2006, we investigate the relationship between the export performance of firms and how their products relate to local comparative advantage. Our key indicator measures the density of the links between a product and the local product space. It hence combines information on the intrinsic relatedness of a good with that on the local pattern of specialization. Our results indicate that exports grow faster for goods that have denser links with those currently produced in the firm's locality. The density of links between products thus seems to yield export-enhancing spillovers. We however also show that this positive effect of product relatedness on export performance is mainly limited to ordinary trade activities and domestic firms. It is also stronger for more productive firms, suggesting that spillover diffusion may be hindered by insufficient absorptive capacity.
Keywords: J10; J14; O14; 330; product space; density; spillovers; export performance; China